Optimizing transparent photovoltaic integration with battery energy storage systems in greenhouse: a daily light integral-constrained economic analysis considering BESS degradation - Mohammadreza Gholami (17032317) (2025)
Greenhouses provide controlled environments for crop cultivation, and integrating semi transparent photovoltaic (STPV) panels offers the dual benefits of generating renewable energy while facilitating natural light penetration for photosynthesis. This study conducts a feasibility analysis of integrating Battery Energy Storage Systems (BESSs) with STPV systems in greenhouse agriculture, considering the Daily Light Integral (DLI) requirement for different crops as the primary constraint. Employing an enhanced Firefly Algorithm (FA) to optimize the PV cover ratio and BESS capacity, the analysis aims to maximize the Net Present Value (NPV) over a 25-year period, serving as the primary economic parameter. By incorporating DLI requirements for various crop types, the study ensures optimal crop growth while maximizing electricity generation. To ensure realistic long-term projections, the analysis incorporates BESS degradation over the 25-year period, accounting for capacity loss and efficiency reduction in energy storage. The results reveal the significant impact of crop type, with various required DLI , and transparency factor on optimized BESS and consequently the NPV of the project. Simulation results show that for crops with high DLI requirements, the feasible range of PVR% in the greenhouse varies from 42 % to 91 %, depending on the STPV’s transmittance factor. Additionally, the study reveals that initial negative revenue is common across all cases, with the highest NPV achieved at $1,331,340 for crops with low DLI requirements and a BESS capacity of 216 kW. Other Information Published in: Renewable Energy Focus License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ref.2025.100679